2021
DOI: 10.3390/diagnostics11091673
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Silent Small Vessel Disease of the Brain in Patients with Obstructive Sleep Apnea Hypopnea Syndrome

Abstract: Obstructive sleep apnea hypopnea syndrome (OSAHS) is associated with increased risk of cerebrovascular disease. The aim of the present study was to investigate the association between the presence of the small vessel disease (SVD) of the brain in patients with OSAHS. The study included 24 patients with moderate to severe OSAHS and 34 healthy volunteers. All the subjects underwent magnetic resonance imaging (MRI) of the brain, in order to sought periventricular white matter (PVWM), deep white matter (DWM) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…OSAHS is a disease involving multiple systems of the whole body, which can cause damage to multiple target organs of the whole body to a certain extent, such as cardiovascular and cerebrovascular diseases, diabetes, pulmonary heart disease, respiratory failure, and cognitive dysfunction. In recent years, studies have shown that the cognitive dysfunction caused by OSAHS patients is mainly mild cognitive impairment, and with the development of the disease, severe cases may evolve into Alzheimer's disease, among which the incidence of cognitive dysfunction is higher in severe OSAHS patients [ 3 ]. Stroke is a kind of cerebral blood circulation disorder with transient or permanent brain dysfunction as the main clinical manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…OSAHS is a disease involving multiple systems of the whole body, which can cause damage to multiple target organs of the whole body to a certain extent, such as cardiovascular and cerebrovascular diseases, diabetes, pulmonary heart disease, respiratory failure, and cognitive dysfunction. In recent years, studies have shown that the cognitive dysfunction caused by OSAHS patients is mainly mild cognitive impairment, and with the development of the disease, severe cases may evolve into Alzheimer's disease, among which the incidence of cognitive dysfunction is higher in severe OSAHS patients [ 3 ]. Stroke is a kind of cerebral blood circulation disorder with transient or permanent brain dysfunction as the main clinical manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable that poor sleep quality in humans may disrupt the removal of neurotoxins, interrupt the drainage of interstitial fluid, and possibly result in dilation of the perivascular spaces. In addition, some studies have demonstrated that poor sleep quality was associated with brain atrophy and WMH which share some risk factors with EPVS (11,12). However, the relationship between EPVS and sleep in humans is scarcely explored.…”
Section: Introductionmentioning
confidence: 99%